Activism in Danish foreign policy: UN, NATO, EU and the Nordic cooperation - Pedersen, Rasmus Brun; Ringsmose, Jesn (Politica, 2017)
This introductory article commences with a brief overview of the existing literature on Danish foreign policy activism. We argue that the concept – activism – is useful in terms of labelling Danish foreign policy in general but also that the notion of activism hampers a more nuanced understanding of Denmark’s recent foreign policy as it relates almost entirely to Danish security policies. To more comprehensively appreciate the true nature of Danish foreign policy, we have to be more precise when operationalizing the concept of activism and engage with a compartmentalized understanding of Denmark’s policies vis-à-vis her international surroundings. We do both in the article’s second main section and we develop a typology for analyzing different types of foreign policies. In the article’s third and last section, we compare four major institutional tracks in Danish foreign policy: EU, NATO, UN and the Nordic track.